A Review of Digital Media Guidelines for Students with Visual Light Sensitivity. Issue 2 (4th March 2021) - Sproul, Janene; Ledger, Susan; MacCallum, Judith
ABSTRACT: Technological developments allow students to access visual information from digital devices as small as phones or as large as whiteboards. Education technology research and policy typically address the software product, yet little research has focused on optimal viewing parameters or the impact it has on student users. Students with light sensitivity (migraine, concussion) potentially face a barrier with e-learning activities in the classroom. This review aimed to identify points of convergence and inconsistency across various literature sources containing guidelines for digital media use by students in schools. Inconsistencies were found between academic, manufacturer and school guidelines. Six parameters were identified for modification on behalf of students with light sensitivity relating to image colour, image flash frequency, duration of viewing, luminance and environmental lighting – both natural and artificial. The findings highlight the need for revision of school policies regarding digital learning environments and awareness raising to support inclusive access and use by students with light sensitivity. Abbreviations : WHO - World Health Organisation; DALY- Disability Adjusted Life Years; ADHD - Attention Deficit Hyperactivity Disorder; BBC - British Broadcasting Corporation; IAW - Interactive Whiteboard; WCAG - Web Content Access Guidelines; ITU - International Telecommunications Union